Analysis Juridical: Collaboration of Pesantren-Regional Governments in Education and Community Empowerment Functions - Shohib Muslim (STAI Syaichona Moh. Cholil Bangkalan, 2022)
The role of Islamic boarding schools in community empowerment education is substantially clearly directed to establishing communication between the pesantren and the surrounding community. This research is a library research study. The processing of this research is more directed at analyzing or processing data that is descriptive, philosophical, and theoretical. The research analysis results conclude that Law Number 18 of 2019 and Presidential Regulation number 82 regulate community cooperation and participation. Collaboration can be carried out by Islamic boarding schools with other national and international institutions. Such partnership is carried out, among others, in the form of student exchanges, competitions, education system, curriculum, funding assistance, training, capacity building, and other forms of cooperation. It is carried out under the provisions of laws and regulations that Islamic boarding schools have been recognized as part of the system—of Indonesian education.